Development of a Neuromuscular Junction Model on Surfaces Modified by Plasma Polymerization - Zuñiga-Aguilar., E.; Godínez, R.; Ramírez-Fernández, O.; Morales., J.; Olayo., R. (Revista Mexicana de Ingenieria Biomedica, 2013)
The aim of this work is to implement a biological model of neuromuscular junctions to study the mechanisms involved in intra and intercellular processes using cell co-cultures. To optimize growth and development of the neuromuscular junction, cells were seeded on plasma polymerized pyrrole which has proven suitable for other types of cell cultures. The cell lines used were motor neuron NG108-15 and skeletal muscle C2C12. Cells were evaluated according to their morphology and electrophysiological characteristics. To observe the expression of specific proteins of the nerve synapse, immunocytochemical techniques were applied using dying antibodies. Proteins localized in nerve terminals were dyed and imaged by fluorescence microscopy. Images of cell co-cultures showed the formation of neuromuscular junctions. The preparation of neuromuscular junctions described in this work will allow the study of the mechanisms involved in their functions.